DEVELOPMENT AND VALIDATION OF AN ANTHROPOMETRIC-BASED TALENT IDENTIFICATION TEST FOR EARLY VOLLEYBALL ATHLETES AGED 6–9 YEARS - Iska Noviardila; Syahrial Bakhtiar; Khairuddin Khairuddin (El Midad, 2025)
Early identification of sport talent is vital for systematic athlete development and long-term success. However, validated tools for detecting early volleyball talent are scarce, especially for children aged 6–9 years. This study developed and validated the Early Volleyball Anthropometric Talent Test (EVATT-6/9) as a reliable and practical instrument based on anthropometric indicators. Using a research and development (R&D) design with a mixed-methods approach, 90 students (45 boys, 45 girls) from three elementary schools in Pekanbaru, Indonesia, were tested on seven indicators: body height, arm span, standing reach, leg length, upper-arm circumference, hand length, and calf circumference. Analyses included Aiken’s V, Exploratory and Confirmatory Factor Analyses, and reliability tests (Cronbach’s ?, ICC). All indicators showed strong content validity (Aiken’s V > 0.90) and excellent reliability (? = 0.87; ICC = 0.89). Two latent factors—upper-body reach/control and lower-body power/support—explained 72.4% of variance, and criterion validity was confirmed (r = 0.68, p < 0.01). EVATT-6/9 is valid, reliable, and practical for early volleyball talent identification in school and grassroots settings.